Pelatihan komunikasi efektif berbasis media sosial bersama ppni komisariat rsud karawang - Siti Nursanti; Firdaus Yuni Dharta; Chaerudin; Syisea Putri Syam; Rifki Nugraha Purnama (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Excess information related to the Covid-19 virus has created a crisis of public confidence in the massively spreading information related to the handling of the Covid-19 pandemic. It is the duty of professionals in the field of communication and health to produce reliable health information. Serving as lecturers and students of Communication Studies at the Faculty of Social and Political Sciences, Singaperbangsa University, Karawang, intends to conduct training to health workers at the Karawang Hospital regarding effective communication in providing health literacy to patients in Karawang Hospital by using social media. The training activities will be conducted online using the zoom.us application. This training activity is expected to improve the skills of health workers to produce health information and disseminate it to the wider community so that the Covid-19 virus problem can be resolved immediately.